Feral horses and alien plants: effects on the structure and function of the Pampean Mountain grasslands (Argentina) - de Villalobos, Ana Elena (2017)
Disturbances can affect the biotic resistance of plant communities and alterations could takeplace in the system, such as the appearance or increase in abundance of new components. Tocharacterize the resistance to disturbance and the aptitude to limit the establishment of alienplants, it is necessary to know the functional and specific diversity of plant communities. Theobjective was to evaluate the effects of grazing by feral horses on the resistance of naturalgrasslands of Argentina to alien plant invasion by means of specific composition and functionalstructure. Two grasslands under continuous grazing by feral horses and two exclosures werestudied. Species composition and functional structure were characterized using species richness,Shannon?s diversity index, functional richness, functional evenness and functional divergence.Alien plant richness and abundance, as well as alien:native plants ratio were determined. Specificcomposition and functional structure were negatively affected by feral horse grazing and thedistribution of alien species in the different functional groups differed in areas with contrastinggrazing histories. The activity of feral horses can modify the abundance of dominant plants andfunctional diversity, thus providing niche opportunities for the establishment of alien plants, inturn affecting the function and structure of the system.